Scientific fundamentals of the formation of state policy in the plant quarantine - Borzykh, А. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
Continually occur thousands of invasions (natural and anthropogenic) harmful organisms into the territory of the country. Alien organisms can acclimatize, take new ecological niches, and compete successfully with local species, sometimes causing irreversible environmental processes and significant economic losses. The development of scientific foundations for identifying and preventing the introduction of regulated pests into the territory of Ukraine involves, first of all, the improvement of the theoretical foundations of quarantine, the development of systems and, in particular, measures to protect the territories from the penetration of the missing and the localization of foci of limited pest infectious organisms.